GSK-3β Inhibition in Birds Affects Social Behavior and Increases Motor Activity - Moaraf, Stan; Rippin, Ido; Terkel, Joseph; Eldar-Finkelman, Hagit; Barnea, Anat (Frontiers in Physiology, 2022)
Glycogen synthase kinase-3 (GSK-3) is a highly conserved serine/threonine protein kinase that plays a central role in a wide variety of cellular processes, cognition and behaviour. In a previous study we showed that its α and β isozymes are highly conserved in vertebrates, however the α gene is missing in birds. This selective loss offers a unique opportunity to study the role of GSK-3β independently. Accordingly, in the present study we aimed to investigate the role of GSK-3β in social behaviour, motivation, and motor activity in zebra finches (Taeniopygia guttata). We did that by selective inhibition of GSK-3β and by using tests that were specifically designed in our laboratory. Our results show that GSK-3β inhibition: (1) Affected social recognition, because the treated birds tended to move closer towards a stranger, unlike the control birds that stood closer to a familiar bird. (2) Caused the treated birds to spend more time in the more middle parts of the cage compared to controls, a behaviour that might indicate anxiety. (3) As the experiment progressed, the treated birds took less time to make a decision where to stand in the cage compared to controls, suggesting an effect on decision-making. (4) Increased in the motor activity of the treated birds compared to the controls, which can be regarded as hyperactivity. (5) Caused the treated birds to pass through a barrier in order to join their flock members faster compared to controls, and regardless of the increase in the level of difficulty, possibly suggesting increased motivation. Our study calls for further investigation, because GSK-3 is well acknowledged as a central player in regulating mood behaviour, cognitive functions, and neuronal viability. Therefore, studying its impact on normal behaviour as we did in the current study, unlike most studies that were done in diseases models, can advance our understanding regarding GSK-3 various roles and can contribute to the discovery and development of effective treatments to repair cognition and behaviour